Comparative Genomics of Clostridioides Difficile Strains: Understanding Toxin Gene Regulation and Resistance Mechanisms - Al-Zubaidy, Zainab H. (American Journal of Biology and Natural Sciences, 2025)
Clostridioides difficile is a leading cause of healthcare-associated infections worldwide, primarily responsible for antibiotic-associated diarrhea and colitis. The pathogenicity of C. difficile is mainly attributed to its large clostridial toxins, TcdA and TcdB, and, in some strains, the binary toxin CDT. Comparative genomics provides valuable insights into the diversity of toxin gene regulation, virulence determinants, and antimicrobial resistance mechanisms across different strains. In this study, we explore genomic variations among representative clinical and environmental isolates to better understand how genetic differences shape pathogenic potential. Analysis of toxin gene loci (PaLoc and CdtLoc) revealed notable heterogeneity in regulatory sequences, transcriptional regulators, and mobile genetic elements influencing toxin expression. Comparative studies further highlighted variations in promoter regions and the presence of accessory genes, suggesting strain-specific modulation of toxin production. These differences may contribute to the variable clinical outcomes observed in patients, ranging from mild diarrhea to severe pseudomembranous colitis. In addition to toxin regulation, antimicrobial resistance determinants were identified across diverse strains. Resistance genes associated with fluoroquinolones, macrolides, tetracyclines, and clindamycin were frequently detected, often located on plasmids, transposons, or integrative conjugative elements. Comparative genomic evidence also indicated the role of horizontal gene transfer in disseminating resistance traits within C. difficile populations. Overall, this work underscores the importance of comparative genomics in elucidating the molecular mechanisms underlying toxin gene regulation and resistance in C. difficile. Understanding these genomic features not only improves our knowledge of its pathogenic diversity but also provides a foundation for developing targeted therapeutic and preventive strategies to combat this major healthcare threat.